Disaster Mitigation Communication Model Using Folk Media - Petrus Ana Andung; Jakobis Johanis Messakh; Meryana Micselen Doko (Penerbit Universiti Kebangsaan Malaysia, 2024)
South Central Timor is the most disaster-prone district in East Nusa Tenggara, Indonesia. The two sub-districts that are prone to floods, landslides and droughts are Kualin and Amanuban Selatan. On the other hand, the communities in these two sub-districts have local wisdom such as koa (an iterative concatenation of acoustic messages diffused successively) and natoni (expressive expositions couched in customary poetic cadence) conduits, which manifest latent potential as tools of traditional communication germane to disaster mitigation. The research aims to find a model of disaster mitigation communication through the use of folk media that can be used as a means of strengthening indigenous peoples' disaster information literacy. The theory used is situational crisis communication theory. Data collection techniques included in-depth interviews, focus group discussions and participant observation. The 26 informants consisted of community members, village officials and local disaster management agencies. Data analysis used thematic analysis techniques with 6 stages of analysis. The research found that the people of South Central Timor utilize koa and natoni as folk media for disaster mitigation purposes. The communication model for disaster mitigation in indigenous communities is to take advance of the responsiveness of folk media to strengthen disaster information literacy. This communicative model, effectuated through grassroots channels, is most compatible with the rustic terrain, which is hampered by circumscribed access to cutting-edge communication technology. Further research is recommended to quantitatively assess the effectiveness of community media use in disaster mitigation.